Controlling the internal microstructure and properties of physically cross-linked PVA hydrogels by the rate of freezing - Trudičová, Monika; Zahrádka, Jan; Sedláček, Petr; Pekař, Miloslav (TANGER Ltd., 2021)
PVA hydrogels can be formed via physical crosslinking (e.g. by cyclic freezing/thawing of aqueous polyvinyl alcohol solutions) or with a chemical cross-linker. Physical crosslinking is more useful for biomedical applications since it contains no harmful cross-linker residues. This work, therefore, focused on studying properties of physically crosslinked hydrogels with different concentrations of polyvinyl alcohol (2.5 to 15 wt%) prepared via cyclic freezing/thawing under different cryogenic conditions: in the liquid nitrogen (-196 degrees C), in two different laboratory freezers (-80 degrees C and -18 degrees C) and the ice bath. Furthermore, the effects of the addition of several cryoprotectants were evaluated. The optical and mechanical properties of the prepared samples were studied, and the microstructure of the hydrogels was observed by scanning electron microscopy after freeze-drying.

PVA hydrogels can be formed via physical crosslinking (e.g. by cyclic freezing/thawing of aqueous polyvinyl alcohol solutions) or with a chemical cross-linker. Physical crosslinking is more useful for biomedical applications since it contains no harmful cross-linker residues. This work, therefore, focused on studying properties of physically crosslinked hydrogels with different concentrations of polyvinyl alcohol (2.5 to 15 wt%) prepared via cyclic freezing/thawing under different cryogenic conditions: in the liquid nitrogen (-196 degrees C), in two different laboratory freezers (-80 degrees C and -18 degrees C) and the ice bath. Furthermore, the effects of the addition of several cryoprotectants were evaluated. The optical and mechanical properties of the prepared samples were studied, and the microstructure of the hydrogels was observed by scanning electron microscopy after freeze-drying.
Controlling the internal microstructure and properties of physically cross-linked PVA hydrogels by the rate of freezing
Keywords: hydrogel; polyvinyl alcohol; rheology; scanning electron microscopy; hydrogel; polyvinyl alcohol; rheology; scanning electron microscopy